Alvos moleculares e celulares do extrato padronizado de Ginkgo biloba L. na supressão condicionada - Zamberlam, Claudia Raquel [UNIFESP] (2017)
The present study investigated the effect of the standardized extract of Ginkgo biloba (EGb) on the steps steps in the memory of fear and the extinction of fear memory. A proposal of foundations in multiple dose doses of extract; different times of treatment and acquisition of extract products; different times of treatment and pharmacological acquisitions by agonists and antagonists of serotonergic type 1A (5-HT1AR), glutamatergic receptors NMDA-type, 2B subunit (GluN2B-NMDA) and GABAA (GABAAR, α1 and α5 subunit) in animals submitted to the chest paradigm, assessed by conditioned suppression rate of licking response. Furthermore, we evaluated changes in gene expression (mRNA and protein) in the dorsal hippocampal formation, the amygdaloid complex, and the prefrontal cortex. Behavioral data suggest an EGb time and dose-dependent effect on modulation of 5-HT1A, GABAA and GluN2B-NMDA receptors as well as a glial fibial acidic protein (GFAP). The behavioural data from conditioned suppression ratio allow us to propose the effect of EGb as a nootropic agent because, in addition to not prevent the acquisition of fear memory, it modulates in a dose-dependent manner the extinction of conditioned fear. Our results show for the first time that the menmonic effect of EGb is correlated with differential expression of GluN2B-NMDA, GABAA-α1, GABAA-α5 receptors and GFAP in the dorsal hippocampal (DHF) and 5-HT1AR receptors in the layer CA3 of hippocampus. However, that either activation of GABAARs (Diazepam) or blocking of GluN2B-NMDAR (Ro 25-6981) or 5-HT1AR ((S) -WAY100135) resulted in impairment in memory acquisition and that treatment with high doses of EGb reversed the deficit by increasing the expression of GluN2B and/or GABAAR-α1 and α5 simultaneously in the CA1 region of the hippocampus. Our data added new insights into the role of α1 and α5 subunits of GABAA and GluN2B-NMDA receptors in DHF as an EGb target. In addition, they point to a parallel involvement of these receptors in the prelimbic (PrL) and infralimbic (IL) areas of the prefrontal cortex (PFC) in the acquisition of conditioned suppression, where acquisition impairment was associated with reduced GluN2B-NMDAR and GABAAR α1 expression in PrL. Furthermore, for the first time in the literature, it shows a colocalization between glutamatergic receptors and astrocytes after treatment with EGb. Our studies have analyze the fear memory extinction through the behavioral and pharmacology approach using selective antagonists administered prior to EGb treatment at the different stages of extinction (training and testing) that provide original data on the effects of EGb as well as in the spontaneous recovery of conditioned fear (Zamberlam et al, 2016). We have shown that treatment with Ro25-6981, given prior to conditioning or prior to extinction training, prevented spontaneous recovery of fear memory reported for EGb 1.0 g.Kg-1. However, treatment with (S)-WAY 100135 or Picrotoxin (GABAA-selective antagonist) prevented the effects of EGb (0.25 or 1.0 g.Kg-1) when administered prior to extinction training. We found decreasing of relative expression of Gabra1 and Gfap and increase of Gabra5 in the DHF of the groups treated with antagonists Ro 256981 and Picrotoxin (GABAA). Our data suggest that the increased Gabra5 seems related with impaired extinction of fear memory. In the prefrontal cortex, a regulation of the receptors seems to occur in the opposite way. Data from the gene expression to groups treated with Ro 25-6981 and (S)-WAY 100135 antagonists suggest that increased in Gabra1 expression in the PFC seems to be associated with fear extinction memory. The results suggest that the effects of EGb are multitarget and depend on the interaction between receptors in a dose-dependent manner. Then, our data suggest that spontaneous recovery is not modulated by gene expression of Grin2b, Gabra1, Gabra5, Htr1a and Gfap in the cenamygdaloid complex. However, modulates diferentially the protein expression in Ce and BLA in the extinction fear memory and spontaneous recover of fear memory. Taken together, our data suggest that the serotonergic, glutamatergic and GABAergic receptors analyzed in this study, as well as astrocytes, are targets of the effects of the standardized extract of Ginkgo biloba on the acquisition and extinction of conditioned suppression in a tissue-dose-time-dependent manner.